Pengaruh Self Efficacy dan Lingkungan Keluarga terhadap Minat Berwirausaha pada Mahasiswa yang Kuliah Sambil Bekerja dengan Norma Subjektif sebagai Variabel Moderasi - Kristian Harefa, Peni; Sirine, Hani (Teewan Journal Solutions, 2025)
Initiating entrepreneurship is not an easy endeavor for students. To embark on entrepreneurship, one must possess a high level of entrepreneurial interest to enhance the chances and motivate the realization of the entrepreneurial venture. Many factors can influence entrepreneurial interest, some of which include self-efficacy and the family environment. Currently, many students are also starting to work while researching, and several reasons underlie this action. However, one of the reasons is to gain experience as a preparation for starting an entrepreneurial venture. The purpose of this research is to investigate the influence of self-efficacy and the family environment on entrepreneurial interest, moderated by subjective norms. The research method employed is quantitative descriptive with a multiple linear regression design. The research involved 100 respondents, specifically students who are working while researching in the city of Salatiga. Data was collected using a combination of snowball sampling and incidental sampling methods. The data analysis method utilized includes the T-test, determination coefficient test, and moderated regression analysis (MRA). The research results indicate that H1 and H2 are accepted. There is a significant positive influence between self-efficacy and entrepreneurial interest (t = 5.436 and sig = 0.000), as well as a significant positive influence between the family environment and entrepreneurial interest (t = 3.454 and sig = 0.001). Meanwhile, H3 and H4 are accepted. The higher the moderation of subjective norms, the more it weakens the influence of self-efficacy on entrepreneurial interest (t = -2.311 and sig = 0.023), and the higher the moderation of subjective norms, the more it weakens the influence of the family environment on entrepreneurial interest (t = -3.641 and sig = 0.000). The determination coefficient test results indicate that self-efficacy and the family environment collectively account for 53% of the influence on entrepreneurial interest.